The generation of wealth in the transportation companies located in the regions of Arequipa, Cusco, Lambayeque and La Libertad, year 2013 and the contribution to the regional gross domestic product - Pachas Fuentes, María Olivia (2017)
Describes the research carried out by the Observatory Tourist of Peru of the Professional School of Tourismand Hospitality of the University of San Martin de Porres, who poses as an aim to see the generation of the grossdomestic product (GDP) of the transportation companies in the regions of Arequipa, Cusco, Lambayeque and LaLibertad; as well as its contribution to the GDP of each region. The methodology used was exploratory, transverse,descriptive and hermeneutic. We gave a quantitative approach, where we applied techniques of accounting andeconomic research of the satellite accounts. The documentary and technical field technique were used. Theuniverse was made up of 100 % of the companies of transport in the regions of Arequipa, Cusco, Lambayeque andLa Libertad. The surveys were applied to executives and heads of establishments.